A Multi-Perspective Proximity View on the Dynamic Head Region of the Ribosomal 40S Subunit - Kerstin Schmitt (MDPI AG, 2021)
A comparison of overlapping proximity captures at the head region of the ribosomal 40S subunit (hr40S) in Saccharomyces cerevisiae from four adjacent perspectives, namely Asc1/RACK1, Rps2/uS5, Rps3/uS3, and Rps20/uS10, corroborates dynamic co-localization of proteins that control activity and fate of both ribosomes and mRNA. Co-locating factors that associate with the hr40S are involved in (i) (de)ubiquitination of ribosomal proteins (Hel2, Bre5-Ubp3), (ii) clamping of inactive ribosomal subunits (Stm1), (iii) mRNA surveillance and vesicular transport (Smy2, Syh1), (iv) degradation of mRNA (endo- and exonucleases Ypl199c and Xrn1, respectively), (v) autophagy (Psp2, Vps30, Ykt6), and (vi) kinase signaling (Ste20). Additionally, they must be harmonized with translation initiation factors (eIF3, cap-binding protein Cdc33, eIF2A) and mRNA-binding/ribosome-charging proteins (Scp160, Sro9). The Rps/uS-BioID perspectives revealed substantial Asc1/RACK1-dependent hr40S configuration indicating a function of the β-propeller in context-specific spatial organization of this microenvironment. Toward resolving context-specific constellations, a Split-TurboID analysis emphasized the ubiquitin-associated factors Def1 and Lsm12 as neighbors of Bre5 at hr40S. These shuttling proteins indicate a common regulatory axis for the fate of polymerizing machineries for the biosynthesis of proteins in the cytoplasm and RNA/DNA in the nucleus.